(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Non-Banking Financial Companies (NBFCs) have become important players in the financial system, complementing the traditional banking system and providing credit facilities to the sections of society which don’t get credit facilities from the banks. In two decades, NBFCs have emerged as a key player in achieving financial inclusion, providing funds for micro, small and medium enterprises (MSMEs), financing infrastructure projects and providing funds to the rural and semi-urban population which has been difficult to access by traditional banking systems. Their agility, the customer-centric service and the innovative financial products allowed them to respond to various financing needs and stimulate economic growth. Although NBFCs have been gaining significance, they have also been facing challenges on financial stability, regulatory compliance, asset quality, liquidity management and corporate governance due to the growth of NBFCs. The infrastructure finance sector has faced risks and challenges, including the Infrastructure Leasing & Financial Services (IL&FS) crisis and the subsequent liquidity crisis in the sector, which have exposed vulnerabilities that need to be addressed through effective regulatory oversight. On its part, the Reserve Bank of India (RBI) has taken several steps to improve supervision, transparency and bring regulatory framework into line with the changing market conditions. This article portrays the changing landscape of the NBFC sector in India and explores its contribution to economic development, the new avenues it presents, its operational hurdles, and the effectiveness of the existing regulatory regimes. It also discusses the importance of balancing regulation to foster innovation and financial stability, consumer protection and sustainable growth in the sector.